2016
DOI: 10.5721/eujrs20164901
|View full text |Cite
|
Sign up to set email alerts
|

3D displacement field retrieved by integrating Sentinel-1 InSAR and GPS data: the 2014 South Napa earthquake

Abstract: In this study the integration of Sentinel-1 InSAR (Interferometric Synthetic Aperture Radar) and GPS (Global Positioning System) data was performed to estimate the three components of the ground deformation field due to the Mw 6.0 earthquake occurred on August 24th, 2014, in the Napa Valley, California, USA. The SAR data were acquired by the Sentinel-1 satellite on August 7 th and 31 st respectively. In addition, the GPS observations acquired during the whole month of August were analyzed. These data were obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 24 publications
(29 reference statements)
1
14
0
Order By: Relevance
“…DeLong et al [2015] identified that both the coseismic and postseismic patterns of vertical deformation along this fault in 2014 occurred over a width of~50 m with no more than 15-20 cm of elevation change. Polcari et al [2016] also identify east downward relative vertical motion of~8 cm across the main fault trace along this part of the fault. This indicates wide, low-angle scarps may, in some settings, be diagnostic of Holocene strike-slip faulting rather than evidence for tectonic quiescence.…”
Section: Implications For Seismic Hazardmentioning
confidence: 71%
See 2 more Smart Citations
“…DeLong et al [2015] identified that both the coseismic and postseismic patterns of vertical deformation along this fault in 2014 occurred over a width of~50 m with no more than 15-20 cm of elevation change. Polcari et al [2016] also identify east downward relative vertical motion of~8 cm across the main fault trace along this part of the fault. This indicates wide, low-angle scarps may, in some settings, be diagnostic of Holocene strike-slip faulting rather than evidence for tectonic quiescence.…”
Section: Implications For Seismic Hazardmentioning
confidence: 71%
“…These include a component of vertical deformation that indicates centimeter‐level uplift on the west side of the fault, consistent with long‐term west side up displacement manifested by higher topography and gravity values west of the fault zone [ Langenheim et al ., ]. This is supported by analyses of lidar data [ DeLong et al ., ] and spaceborne SAR and GPS data [ Polcari et al ., ].…”
Section: Comparison Of Slip Distribution From Field and Remote Sensinmentioning
confidence: 99%
See 1 more Smart Citation
“…If the ratio is between 25 % and 75 %, both regional and local-scale impact factors are important. However, the nugget effect cannot identify the sources affecting land subsidence distribution (Song et al, 2018).…”
Section: Geographical Semi-variogram Analysismentioning
confidence: 99%
“…The advent of remote sensing and, more specifically, the radar satellite data have provided new means of research to the scientific community for earthquake studies [22][23][24][25][26][27]. The aim of this study is to examine the fault segmentation of the CTF, taking advantage of new remote sensing radar data.…”
Section: Introductionmentioning
confidence: 99%